Performance Evaluation of Advanced Unit-Dose Drug Dispensing Machines for Hospital Settings: A Case Study (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Unit-dose drug dispensing machines represent a significant advancement in hospital pharmacy operations, enhancing medication safety, efficiency, and inventory management. This paper evaluates the performance of the latest generation of unit-dose dispensing machines designed for hospital settings, focusing on pills. Metrics such as dispensing accuracy, speed, error reduction, and cost-efficiency were analyzed. Findings indicate that the new machines substantially reduce medication errors and improve workflow efficiency while providing a scalable solution for large healthcare institutions.